The impact of air pollutants with Hydrocarbons, except for Methan (NMHC), on the increase in the number of cancer patients in general,(Lung and Bladder ) cancer ,especially in Basra governorate - Dhafera Mhajar Toamma Waleed Hameed Ahmed AL- Mosuwi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Basra Governorate suffers from a significant air pollution from multiple sources, the most important of which is the oil industry which is considered the main source of Hydrocarbon emissions. In addition to vehicle exhausts, thermo-power plants, spread of private generators, and random burning operations in landfills and others. Therefore, this research was prepared to show the extent of the impact of air pollution, especially with hydrocarbons, except for methane, on the incidence of various cancerous diseases, especially cancer (lung and bladder) in the districts of Basra Governorate by analyzing the data and annual rates of concentrations of hydrocarbons recorded in specific monitoring stations. The ambient air of the Basra Environment Directorate for the period (2015-2018) was used, and the population statistics of the province’s districts and the numbers of people with cancerous diseases were used to determine the districts with the highest rates of infection (per 100,000 people. The research dealt with the rates of infection per 100,000 people with bladder and lung cancer in particular (males and females) and the comparison between them in the governorate. Through the study, it was found that the concentrations of hydrocarbons, except for methane (NMHC), in all monitoring points were several times higher than the permissible limits (according to national determinants) (ppm0.24) per 3 hours. It was also found that Basra governorate witnesses an annual increase in the incidence of cancerous diseases per 100,000 people (and that air pollution is closely related to this increase, especially in some types of cancer (lung and bladder).